The constitutionality of section 7(3) of the Divorce Act 70 of 1979, with specific reference to the date of conclusion of the marriage and the matrimonial property system as limitations to the application of section 7(3) - Van Schalkwyk, L.N. (Llewelyn Neil), 1952- (University of Pretoria, 2015)
Mini Dissertation (LLM)--University of Pretoria, 2015.